PENERAPAN SANKSI ADAT MELAYU KERAJAAN SIAK SRI INDRAPURA TERHADAP KEKERASAN DALAM RUMAH TANGGA - Nabella Puspa Rani (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2016)
Domestic violence (KDRT) problems in Indonesia each year has increased high and then women often become victims. Violence against women has become an important issue and cause anxiety in every country in the world, including developed countries are said to be highly appreciative of human rights. The legal culture of society, especially the Malay culture that is still embraced by the Siak Sri Indrapura people have the perception that the household is a private area and a disgrace that should not be known or told to others. It is also one of the inhibiting factors in law enforcement on Domestic violence (KDRT) in Siak Sri Indrapura. The application of traditional sanctions in Siak Sri Indrapura still entrenched in people’s lives. The existence of traditional law is still maintained by the Siak Sri Indrapura community until today, in the form of dispute resolution through traditional law always used the kinship principle and the principle of the peace, based on the basis of deliberative consensus.